Simulation of Customer Flows in a Policlinic - Brožek Josef; Baše Lukáš; Fiala Vladimír; Samotán Vojtěch (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The topic focuses on Rockwell Arena simulation of customers flow in policlinic.
Simulace zákaznických proudů v polyklinice
Keywords: Simulation; Customer; Flows; Policlinic; Simulace; zákaznických; proudů; polyklinice